QOL-17. Neurocognitive outcomes after treatment for medulloblastoma with reduced primary site target volume margins. (3rd June 2022) - Larkin, Trisha; Lin, Tong; Ashford, Jason M; Onar-Thomas, Arzu; Gajjar, Amar; Conklin, Heather M; Merchant, Thomas
Abstract: PURPOSE: Children treated for medulloblastoma (MB) undergo intensive multimodality treatment compromising surgery, irradiation, and chemotherapy, which is associated with a significant risk of neurocognitive deficits. Successive multicenter frontline treatment protocols have introduced reduced posterior fossa boost margins for cranial irradiation for sparing collateral tissue and preserving function. This study examines neurocognitive outcomes in the setting of reduced primary site target volume margins in children treated for MB. PATIENTS & METHODS: Prospective longitudinal neurocognitive data were collected from newly diagnosed patients with MB (n = 372, ages 3-21 years) enrolled on one of two sequential multicenter clinical protocols between 1996 and 2012. The treatment regimen included surgery, risk-adapted craniospinal irradiation with a posterior fossa boost with restricted clinical target volume (CTV) margins (2 cm and 1 cm), and dose-intensive chemotherapy. Comparative analysis of neurocognitive outcomes was performed using linear mixed-effects models. RESULTS: Intelligence quotient (IQ) scores were better preserved in average-risk patients who received treatment using a clinical target volume with a lesser margin of 1 cm (p < 0.0099). Findings were consistent with prior studies on measures of academics including reading performance, mathematical reasoning, and spelling across both risk groups regardless of CTV. CONCLUSION: This study presents compelling evidence in favor of restricted CTVs for preserving IQ without sacrificing treatment efficacy in average childhood MBs.